Quantum corrections to dynamical holographic thermalization: entanglement entropy and other non-local observables - Baron, Walter Helmut (2013)
We investigate the thermalization time scale in the planar limit of the SU(N) N=4 SYM plasma at strong yet finite ´t Hooft coupling by considering its supergravity dual description, including the full O(alpha´^3) type IIB string theory corrections. We also discuss on the effects of the leading non-planar corrections. We use extended geometric probes in the bulk which are dual to different non-local observables in the N=4 SYM theory. This is carried out within the framework of dynamical holographic thermalization.